Experimental research on square steel tubular columns filled with steel-reinforced self-consolidating high-strength concrete under axial load - Zhu, Meichun; Liu, Jianxin; Wang, Qingxiang; Feng, Xiufeng (Engineering structures, 2010)
A new design model for steel–concrete composite columns, namely square steel tubular columns filled with steel-reinforced self-consolidating high-strength concrete, is proposed. In this type of steel–concrete composite column, a steel section is inserted into the square steel tube and self-consolidating high-strength concrete is filled into the tube. Eighteen composite column specimens were tested under axial compression. The effects of concrete strength, width-to-thickness ratio, length-to-width ratio, and ratio of steel section on the strength and deformation characteristics of these composite columns are discussed. The experimental results indicate that the encased steel section can restrain the generation of diagonal shear cracks in the core concrete thus changing the failure mode and the post-yield behavior of short composite columns. Formulas for calculating the ultimate strength of centrally loaded composite columns are proposed. The calculated values are in good agreement with the test results.